ASSESSMENT OF THE CURRENT GERIATRIC PHARMACEUTICAL CARE IN THE UNITED ARAB EMIRATES - OSAMA MOHAMED IBRAHIM; RANA IBRAHIM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The primary goal of this study is to assess the current geriatric pharmaceutical care and patient satisfaction among elderly patient. Another aim is to increase the awareness among pharmacists in providing better guidelines for proper geriatric pharmaceutical care in the United Arab Emirates (UAE). Methods: A pilot observational study was done through the dissemination of cross-sectional surveys among pharmacists and geriatrics in the Emirates of Abu Dhabi, Dubai, and Sharjah. Three hundred and eight pharmacists and 110 geriatric patients were randomly selected to participate in the study. Results: Among pharmacists participating in the study, 32.1% were from Abu Dhabi, 37.6% from Dubai, and 30.1% from Sharjah. Geriatric patients who participated from Abu Dhabi were 30.0%, 38.1% were from Dubai, and 31.8% were from Sharjah. Geriatrics level of satisfaction was higher in Abu Dhabi compared to Sharjah and Dubai (p=0.0005). Pharmacists in Sharjah and Dubai had higher interest in taking special courses on how to deal with elderly patients compared to pharmacists in Abu Dhabi (p<0.0001). Conclusions: Geriatrics satisfaction toward pharmaceutical care is not the same in all Emirates of the UAE. This calls for implementing diverse measures such as providing training courses for pharmacists specialized in geriatrics care, which aims to provide a high-quality pharmaceutical care to all geriatrics in the UAE.